A Model for Predicting Skills and Competences of Y and Z Generation Members for Industry 4.0 - Silviu N. SURU; Gabriela I. PROSTEAN; Petra L. PROSTEAN (Communications of International Proceedings, 2021)
At the moment, with the accelerated development of Industry 4.0 and the massive digitalization that makes the transition to the Smart Era, there is a focus on the human resources sector in particular, due to the fact that it is known that well-equipped employees are some of the key points in this system. Forecasts of the skills and competencies needed for existing positions create real niches for advancement in an increasingly dynamic and efficient environment. At the moment, two great generations meet in this process of automation, being about the generation of Millennials, also called generation Y and those who were born in the heyday of the Digital Age, generation Z, and these as they share and allocate their resources, tasks and get involved in the work process is a real source that can be explored. In this paper we propose a conceptual model that classifies the competencies required in Industry 4.0 through a comparative analysis between the strengths of each generation of the two mentioned above, a model that can be used in the selection and recruitment process and can find the right people for each section.
Keywords: Competencies; Generation Z; Generation Y; Conceptual Model; Industry 4.0